Molecular epidemiology and antibiotic resistance of staphylococci other than Staphylococcus aureus in children in Cape Town, South Africa - Ocloo, Remous; Newton-Foot, Mae; Ziebuhr, Wilma; Whitelaw, Andrew Christopher (Frontiers in Microbiology, 2023)
Introduction Staphylococci other than Staphylococcus aureus (SOSA) have emerged as significant pathogens in healthcare settings, particularly among patients with indwelling devices and immunocompromised individuals. Staphylococcus epidermidis, Staphylococcus haemolyticus and Staphylococcus hominis are the most common commensal SOSA species and are implicated in infections such as endocarditis and bacteremia. SOSA infections in neonates and children have been reported globally. Recent increases in antibiotic resistance and virulence among SOSA strains in clinical settings have highlighted the need to describe the reservoirs of SOSA to enable monitoring of these emerging pathogens. Methods Stool samples were collected from 150 healthy children from Cape Town communities between 2017 and 2020. Staphylococci were isolated, identified using mass-spectrometry, and antimicrobial susceptibility testing and Illumina whole genome sequencing were performed. Results Among the participants, 50 (33.3%) were colonized by SOSA, with S. haemolyticus (n = 38; 25.3%) being the most common, followed by S. hominis (n = 5; 3.3%) and Mammalicoccus sciuri (n = 5; 3.3%). Out of the 77 initially isolated S. haemolyticus strains, 23 were identified as Staphylococcus borealis through whole genome sequencing. All S. haemolyticus isolates (n = 49) were methicillin resistant, with 65.3% (n = 32) harbouring mecA. In S. haemolyticus, SCCmec type VIII(4A) was detected in 42.0% of ST9 isolates while non-mecA methicillin resistant S. haemolyticus isolates were mostly ST49 (41.1%). Additionally, 16 (50.0%) S. haemolyticus strains contained non-typeable SCCmec elements. Discussion High rates of methicillin resistance were identified among colonizing SOSA in Cape Town, increasing the risk of transmission to clinical settings. This study also identified a new species, S. borealis, for the first time in Africa.